Overview of beneficial effects of (Poly)phenol metabolites in the context of neurodegenerative diseases on model organisms - Carregosa, Diogo (2021)
Funding Information: Funding: This work has received funding from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation programme under grant agreement No 804229. iNOVA4Health Research Unit (LISBOA—01–0145—FEDER—007344), which is cofunded by Fundação para a Ciência e Tecnologia (FCT)/Ministério da Ciência e do Ensino Superior, through national funds, and by FEDER under the PT2020 Partnership Agreement, is acknowledged. Authors Aβ—Amyloid beta; CAT—catalase; NF–κB—Nuclear factor kappa–light–chain–enhancer of activated B cell; GSK— Glycogen synthase kinase; GSH—glutathione; APP—Amyloid precursor protein; ROS—Reactive Oxygen Species; TNF— Tumor necrosis factor; JNK—c–Jun N–terminal kinases; SOD—Superoxide Dismutase; Tg—transgenic; PPAR— Peroxisome proliferator–activated receptor alpha; LPS—lipopolysaccharide; MPTP—1—methyl–4—phenyl–1,2,3,6— tetrahydropyridine. 1 (Poly)phenol metabolites are named accordingly the recommendations recently published [32], however the name cited in the original publications where the effect is described is indicated in brackets. ↑—increased ↓— decreased. Funding Information: would like to acknowledge FCT for financial support of D.C (2020.04630.BD), R.M (CEEC/04567/CBIOS/2020) and S.F (UIDP/BD4/04567/2020). Funding Information: This work has received funding from the European Research Council (ERC) under the European Union?s Horizon 2020 research and innovation programme under grant agreement No 804229. iNOVA4Health Research Unit (LISBOA?01?0145?FEDER?007344), which is cofunded by Funda??o para a Ci?ncia e Tecnologia (FCT)/Minist?rio da Ci?ncia e do Ensino Superior, through national funds, and by FEDER under the PT2020 Partnership Agreement, is acknowledged. Authors would like to acknowledge FCT for financial support of D.C (2020.04630.BD), R.M (CEEC/04567/CBIOS/2020) and S.F (UIDP/BD4/04567/2020). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.